Flexural strength of a pressable lithium disilicate ceramic: influence of surface treatments - Sato, Tabata do Prado [UNESP]; Cotes, Caroline [UNESP]; Yamamoto, Lígia Tiaki [UNESP]; Rossi, Natalia Rivoli [UNESP]; da Cruz Macedo, Vanessa [UNESP]; Kimpara, Estevão Tomomitsu [UNESP] (Springer Nature, 2013)
The aim of this paper was to evaluate the influence of different surface treatments on the flexural strength of a pressable lithium disilicate ceramic. Sixteen bars (16x2x4 mm) were made, divided into subgroups (n = 10), and the following surface treatments were done: C - no treatment; H - etching with 5% hydrofluoric acid; HC - etching with 5% hydrofluoric acid, silanization, and cementation; N – etching with 5% hydrofluoric acid, neutralization with supersaturated solution of sodium bicarbonate, silanization, and cementation; U – etching with 5% hydrofluoric acid, ultrasonic cleaning in distillated water, silanization, and cementation; NU - etching with 5% hydrofluoric acid, neutralization with supersaturated solution of sodium bicarbonate, ultrasonic cleaning in distillated water, silanization and cementation. The three points flexural strength was performed 24 h after cementation and the data were analyzed using one-way ANOVA and Tukey’s tests (p-value = 0.05). The results showed that the surface treatment had a significant effect (p-value < 0,05) on the flexural strength of the studied ceramic. The N and NU groups showed lower flexural strength than other groups. Thus, it was concluded that neutralization with supersaturated solution of sodium bicarbonate, followed or not by ultrasonic cleaning results in lower mechanical strength of a pressable lithium disilicate ceramic. The etching with 5% hydrofluoric acid did not reduce the flexural strength of this ceramic type.
Keywords: Dental ceramic; Flexural strength; Hydrofluoric acid; Surface treatment